Decreased cerebral blood flow and hemodynamic parameters during acute hyperglycemia in mice model observed by dual‐wavelength speckle imaging. Issue 8 (21st April 2019) - Shemesh, David; Bokobza, Naor; Rozenberg, Konstantin; Rosenzweig, Tovit; Abookasis, David
Abstract : In this study, we use dual‐wavelength optical imaging‐based laser speckle technique to assess cerebral blood flow and metabolic parameters in a mouse model of acute hyperglycemia (high blood glucose). The effect of acute glucose levels on physiological processes has been extensively described in multiple organ systems such as retina, kidney, and others. We postulated that hyperglycemia also alters brain function, which in turn can be monitored optically using dual‐wavelength laser speckle imaging (DW‐LSI) platform. DW‐LSI is a wide‐field, noncontact optical imaging modality that integrates the principles of laser flowmetry and oximetry to obtain macroscopic information such as hemoglobin concentration and blood flow. A total of eight mice (C57/BL6) were used, randomized into two groups of normoglycemia (control, n = 3) and hyperglycemia ( n = 5). Hyperglycemia was induced by intraperitoneal injection of a commonly used anesthetic drug combining ketamine and xylazine (KX combo). We found that this KX combo increases blood glucose (BG) levels from 150 to 350 mg/dL, approximately, when measured 18 minutes post‐administration. BG continues to increase throughout the test period, with BG reaching an average of 463 ± 20.34 mg/dL within 60 minutes. BG levels were measured every 10 minutes from tail blood using commercially available glucometer. Experimental results demonstrated reductions in cerebral blood flow (CBF) by 55%, tissue oxygen saturation (SO2 ) by 15%, and cerebral metabolic rate of oxygen (CMRO2 ) by 75% following acute hyperglycemia. The observed decrease in these parameters was consistent with results reported in the literature, measured by a variety of experimental techniques. Measurements with laser Doppler flowmetry (LDF) were also performed which confirmed a reduction in CBF following acute hyperglycemia. In summary, our findings indicate that acute hyperglycemia modified brain hemodynamic response and induced significant changes in blood flow and metabolism. As far as we are aware, the implementation of the DW‐LSI to monitor brain hemodynamic and metabolic response to acute hyperglycemia in intact mouse brain has not been previously reported. Abstract : Hyperglycemia is characterized by an abnormally high concentration of glucose measured in circulating blood. Because the brain is dependent on a continuous supply of glucose as its principal source of energy and metabolism, changes in blood glucose concentration directly affect cerebral function. Dual‐wavelength laser speckle imaging was used and show significant brain hemodynamic and metabolic changes following acute hyperglycemia in an intact mouse head indicates impairment in global brain function.